An overview of hydrogels and their role in transdermal drug delivery - Ahsan, Anam; Tian, Wen-Xia; Farooq, Muhammad Asim; Khan, Daulat Haleem (International journal of polymeric materials, 2021)
Hydrogels are basically three-dimensional network structures which are formulated from specific natural and synthetic polymers. They have the ability to absorb and carry sufficient quantity of water in their porous structure. Hydrogels can be formulated from natural as well as synthetic polymers. The characteristics of an ideal hydrogel are good permeability, biocompatibility, flexibility and viscoelasticity. There are numerous technologies and method of preparation for hydrogels which are briefly discussed in this review. There are various routes of hydrogel drug delivery into the body including oral, rectal, ocular, subcutaneous, rectal, vaginal and transdermal routes. Hydrogels are suitable candidates for drug delivery as they are biocompatible and can also be degraded when made from bio degradable polymers. Now-a-days hydrogels are extensively used for drug delivery. Hydrogels have much biomedical and pharmaceutical application, among which transdermal drug delivery is remarkable. The formulation of hydrogel-based patch has recently gained much importance because of its unique properties. Hydrogels which are mostly synthesized from hydrophilic polymers have the capacity to hold substantial amount of water ranging from 10-20% and may goes up to 1000's times of their dry weight. This substantial amount of water in hydrogels plays an important role in skin elasticity and moisturization making them suitable dosage form for topical use. In this review, we have briefly described the hydrogels, their types and classification, characteristics, method of preparation, different monomers and polymers used in their formulation, their applications in different fields particularly their role in topical drug delivery is elaborated.